A meta-analysis of the association between vitamin D supplementation and the risk of acute respiratory tract infection in the healthy pediatric group - Fang, Qiongyan; Wu, Yingting; Lu, Jie; Zheng, Huaiyu (Frontiers in Nutrition, 2023)
No previous meta-analysis had explored the association between vitamin D supplementation in healthy pediatrics and the risk of acute respiratory tract infections (ARTIs). Thus, we meta-analyzed the current evidence in this regard to provide sufficient knowledge about this risk-benefit ratio for vitamin D supplementation in this specific age group. We searched seven databases for randomized controlled trials (RCTs) that investigated the effect of vitamin D supplementation and ARTIs risk on a healthy pediatric population (0-18 years old). Meta-analysis was performed through R software. We included eight RCTs after the screening of 326 records according to our eligibility criteria. There were comparable infection rates between Vitamin D and placebo groups (OR= 0.98, 95% CI= 0.90-1.08, P-value= 0.618), with no significant heterogeneity among the included studies (I2= 32%; P-value= 0.220). Moreover, there was no significant difference between the two vitamin D regimens (OR= 0.85, 95% CI= 0.64-1.12, P-value= 0.323), with no considerable heterogeneity among the included studies (I2= 37%; P-value= 0.208). However, there was a significant reduction in Influenza A rates in the high-dose vitamin D group compared to the low dose one (OR= 0.39, 95% CI= 0.26-0.59, P-value< 0.001), with no heterogeneity among the included studies (I2= 0%; P-value= 0.718). Only two studies of 8,972 patients reported different side effects, with overall acceptable safety profile. Regardless of the dosing regimen used or the type of infection, in the healthy pediatric group, there is no evident benefit of using vitamin D to prevent or reduce the ARTI rates.